PENGARUH PERPUTARAN AKTIVA LANCAR TERHADAP RETURN ON INVESTMENT PADA PT. MATAHARI PUTRA PRIMA TBK. PERIODE 2009-2016 - Rizal Ma'ruf Amidy Siregar (KOLEGIAL, 2017)
Return on Investment (ROI) PT Matahari Putra Prima, Tbk. has a downward trend. The downward trend in ROI is due to lower profit margins are affected by inventory turnover, receivable turnover, and cash turnover. The purposes of this research are to determine the effect of inventory turnover on ROI, receivable turnover on ROI, cash turnover on ROI and inventory turnover, receivable turnover and cash flow turnover simultaneously to ROI. The research analyzed by multiple linear regression. The results showed that there is an influence of inventory turnover and cash turnover to ROI. Accounts Receivable Turnover has no effect on ROI. Simultaneously inventory turnover, receivable turnover, and cash turnover on ROI. The value of determination coefficient (R square) of 0.298 means variation of inventory turnover, receivable turnover and cash turnover can explain by ROI variable equal to 29,8 percent. The rest of 70.2 percent is explained by other variables outside the model.